Effect of Commonly Used Pediatric Antibiotics on Gut Microbial Diversity in Preschool Children in Burkina Faso: A Randomized Clinical Trial. (2nd November 2018) - Oldenburg, Catherine E; Sié, Ali; Coulibaly, Boubacar; Ouermi, Lucienne; Dah, Clarisse; Tapsoba, Charlemagne; Bärnighausen, Till; Ray, Kathryn J; Zhong, Lina; Cummings, Susie; Lebas, Elodie; Lietman, Thomas M; et al.
Abstract: Background: Exposure to antibiotics may result in alterations to the composition of intestinal microbiota. However, few trials have been conducted, and observational studies are subject to confounding by indication. We conducted a randomized controlled trial to determine the effect of 3 commonly used pediatric antibiotics on the intestinal microbiome in healthy preschool children. Methods: Children aged 6–59 months were randomized (1:1:1:1) to a 5-day course of 1 of 3 antibiotics, including amoxicillin (25 mg/kg/d twice-daily doses), azithromycin (10 mg/kg dose on day 1 and then 5 mg/kg once daily for 4 days), cotrimoxazole (240 mg once daily), or placebo. Rectal swabs were obtained at baseline and 5 days after the last dose and were processed using 16S rRNA gene sequencing. The prespecified primary outcome was inverse Simpson's α-diversity index. Results: Post-treatment Simpson's diversity was significantly different across the 4 arms ( P = .003). The mean Simpson's α-diversity among azithromycin-treated children was significantly lower than in placebo-treated children (6.6; 95% confidence interval [CI], 5.5–7.8; vs 9.8; 95% CI, 8.7–10.9; P = .0001). Diversity in children treated with amoxicillin (8.3; 95% CI, 7.0–9.6; P = .09) or cotrimoxazole (8.3; 95% CI, 8.2–9.7; P = .08) was not significantly different than placebo. Conclusions: Azithromycin affects the composition of the pediatric intestinal microbiome. The effect of amoxicillin and cotrimoxazole on microbiome composition was less clear. Clinical Trials Registration: clinicaltrials.gov NCT03187834.